If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/4(8x-3)=-3
We move all terms to the left:
3/4(8x-3)-(-3)=0
Domain of the equation: 4(8x-3)!=0We add all the numbers together, and all the variables
x∈R
3/4(8x-3)+3=0
We multiply all the terms by the denominator
3*4(8x-3)+3=0
Wy multiply elements
12x(8+3=0
| 2−–6p=–88 | | (2g-3)/2=-4(g-1) | | 8+3n=65 | | 2-6p=88 | | 0.5(2g-3)=-4(g-1) | | 4x+5+6x+3+5x+7=90 | | 12y+5=17 | | 23x=−1/2x+5 | | 4z^2+18z-52=0 | | X/5+1/4-2=3/2x | | c/2+5=19 | | 3c+9=48 | | x-23=60 | | 2.4+4.9=x+26.3 | | 69=x^2+4x | | 6/11-1/2x=3/22x-1 | | 30x+55=325 | | 7.1x-3.4=32.1 | | 1/2(2g-3)=-4(g-1) | | 4x+-43=2x+31 | | m/9-1=−2 | | 5=1.05^x | | 5.1x-3.7=6.5 | | 12m2+58m+70=0 | | 66x+82=6782 | | -5x+2(2x-5)=-11 | | 543x-24(x+15)=24x | | X+1/5=1/2-1/3x | | y+90=6y-10 | | 8=2t^2-6t | | 33/4-n=15/8 | | c/9+12=22 |